Standardization of technique or evaluation sf wheat (Triticum aestivum) - SINGH, R N; PRASAD, D; SINGH, V; SINGH, A K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2001-2002 to 2003-2004 crop seasons to develop an ope11 field technique for (lac evaluation of wheat (Triticum aestivum L. emend. Fiori and Paol.)genotypes for resistance against spot blotch caused by Cochliobolus sativus(Ito & Kurib) Drechs. ex Dastur under artificial epiphytotics in thc hot spot area of eastern India. Consecutive inoculations of susceptible wheat variety ’I-IP 1633’ using aqueous spore suspension of Faizabad strain of the pathogen containing 8-10 eonidiaolniicrosciopic field undcr 10 X in tile open field with one light irrigation 3 days prior to and post-inoculation, at crop growth stagcs 47 and 57 resulted in severe epipliytoyic (score 89). This technique on 3 years testing gave reproducible results comparable with those obtained under controlled polyhouse technique . Three hundred ninety-four genotypes evaluated using this technique yielded two, namely ’IBWSN 8 1’ and ’SAWSN 12’ resistant and 103 moderately resistant genotypes.